Land Use and Cover Change Patterns in Lower Moiben Sub-County Catchment Area, Kenya - Koech Jemutai Mercy; Sang Catherine Chebet; Daudi Fatuma Abdi (African Journal of Education,Science and Technology (AJEST), 2025)
The changes in land use patterns in Lower Moiben Sub-County catchment area are examined in this study, with a focus on the change between 1995 and 2024. Major land use changes have occurred in the Sub-County catchment area because of socio-economic developments, farming activities, and increased population. Changes in land use that result from the conversion of forests to agricultural land, especially for livestock grazing and increased crop lands, growth of built areas, among others, have affected water supplies and hydrological balance for communities within the catchment. The study used GIS and remote sensing data to assess land use patterns over time and space and also household interviews to understand the observed land use changes. The results shows that there is expansion of croplands (from 51.48% to 77.67%) and built areas (from 0.80% to 4.21 %). Some had slight increase in general, such as, forests (30.53% to 31.22%) and rangeland (12.69% to13.65%) though it is reduction from previous years. The results shows how human activity affects land use/land cover change (LULCC), indicating that whereas certain changes such as increase in built areas mean better development, others changes such as reduced forests may lead to water scarcity. These findings shows that efficient land use management are required in the catchment. These results are useful to policymakers, local communities, and environmental organizations who are strategizing on balancing between development and sustainable land use practices.